Organisational communication towards work-life balance in achieving working homeostatic at JOOX Indonesia - Dewi Widowati; Vidya Alisya; Yuniarti Rahayu; Mufid Salim; Steven Sakasasmita (Jurnal Studi Komunikasi, 2023)
This study aims to observe the implementation of internal communication within the company and how the company implements the work-life balance of its employees. This study utilises the Organisational Control Theory from Phillip Tompkins and George Cheney in Littlejohn and Foss, which is stated in four ways: simple control, technical control, bureaucracy, and conservative control, and uses the concept of work-life balance from Fisher et al., where there are four dimensions of forming a work-life balance: work interference with personal life, personal life interference with work, work enhancement of personal life, and personal life enhancement of work. The results of the study found that employees' work-life balance is obtained unequally by all employees. A hierarchy within the company shows no equal position in the organisation. The managerial position levels and above feel like they have more work-life balance than ordinary employees.